NEW FLAVONOID COMPOUND FROM ALLIUM HOOKERI THWAITES AS A GASTROPROTECTIVE AGENT - Singh, Khumanthem Deepak; Chetia, Dipak; E., Biplab D. (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: The main objective of this study was to investigate the antiulcer potential of an isolated flavonoid compound from Allium hookeri (AH). Methods: Oral administration of ethanol-induced ulcer to the mucosal layer of the stomach in the rats. The ulcer score and percentage protection was calculated from the stomach and gastric mucosal scrapping was carried out for the biochemical studies. Antioxidant study was carried out in liver and histopathological study of the ulcer stomach was performed. Results: Phytochemical investigation of methanolic extract of AH (MEAH) leaves afforded a new flavonoid compound characterized as 3, 5, 6-trihydroxy-2-(4-hydroxy-3-(6-hydroxy-4, 5, 6, 7-tetrahydro benzofuran-7-yl) phenyl-7-methoxy-4H-chromen-4-one (Compound 1). The flavonoid compound at the dose of 5 mg/kg showed a significant change in ulcer index by reducing the ulcer index and increased in percentage protection. It also increased the in vivo antioxidant activity by increasing the superoxide dismutase (SOD), glutathione (GLU) and catalase (CAT) levels. The isolated compound reversed the increase of mucin content in the mucosal scrapings. The histopathology study showed the reversed of normal gland texture in the mucous layer of the standard and compound 1 treated stomach when compared to the negative control. Conclusion: Present findings demonstrated the significant antiulcer activity and antioxidant activity of the isolated flavonoid compound as the supporting factor.